On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900 - Grismer, L. Lee; Quah, Evan S. H.; Duzulkafly, Zaharil; Yambun, Paul (Zootaxa, 2018)
A reassessment of the taxonomy of Lygosoma bampfyldei based on morphology and color pattern indicates that it is a species complex containing L. bampfyldei Bartlett, 1895 from the Rajang River, Sarawak and Croker Range, Sabah in East Malaysia; L. peninsulare sp. nov. from Bukit Larut, Perak and 13.5 km east of Jeli, Kelantan, Peninsular Malaysia; L. kinabatanganensis sp. nov. from the Kinabatangan District, Deramakot camp (=Deramakot Sabah Forestry Department), Sabah, East Malaysia; and L. schneideri Werner, 1900 from Djapura, Indragiri, Sumatra, Indonesia—resurrected herein from the synonymy of L. bampfyldei. The new taxonomy aligns itself well with a growing body of literature demonstrating that semi-fossorial and fossorial Sundaic skinks are more diverse than previously considered.